Pengaruh Efikasi Diri dan Pengetahuan Manajemen Keuangan Bisnis Terhadap Intensi Berwirausaha - Zarah Puspitaningtyas (Lembaga Penelitian & Pengabdian pada Masyarakat (LPPM) Universitas Mikroskil, 2017)
The intention of entrepreneurship is the intention or determination of individual to become entrepreneurs. Before starting entrepreneurship, it takes a commitment within the individual. The commitment is represented in the entrepreneurship intention, that there is an intention to carry out the planned entrepreneurial action. There are many factors that affect the intent of entrepreneurship, including self-efficacy and knowledge. Self-efficacy is a belief in self-abilities arising from individual experience and forming a consistent pattern of behavior. Knowledge that an individual possesses can influence his belief to behave in accordance with that belief. Knowledge in this paper is focused on knowledge of business finance. This paper aims to analyze the influence of self efficacy and the level of knowledge of business finance management to the entrepreneurship intentions of Business Administration students, University of Jember, force of 2015 and 2016. Respondents numbered 97 students, which was determined by using purposive sampling technique. Data analysis was done using multiple linear regression method. The results of the analysis prove that self efficacy has a significant effect on the intention of entrepreneurship. Meanwhile, the level of knowledge of business financial management does not affect the intentions of entrepreneurship.